2021
DOI: 10.1155/2021/1749298
|View full text |Cite
|
Sign up to set email alerts
|

Social Norms Matter: University Students’ Misbehaviors in the Metro Carriage

Abstract: Metro travelers’ travel experience is highly influenced by fellow passengers’ misbehaviors such as eating or littering in the carriage and sound blaster, which are common in the metro carriage. Although operators have implemented various regulations to reduce misbehavior, little theoretical research has investigated such behavior motivators to provide targeted guidelines for specific passenger segments. To this end, this study explores how demographic and perceived social norms of university students affect th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…The insignificant gender differences for the seat yielding behavior on public transportation are consistent with the previous studies explaining the variations of significant gender differences for anti-social behaviors ( 37 , 49 ) and seat yielding behavior on public transportation ( 38 ). Educational interventions should target postgraduates or highly qualified people to encourage yielding seat behaviors as they were reluctant to yield seats, possibly because of their busy life routine.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The insignificant gender differences for the seat yielding behavior on public transportation are consistent with the previous studies explaining the variations of significant gender differences for anti-social behaviors ( 37 , 49 ) and seat yielding behavior on public transportation ( 38 ). Educational interventions should target postgraduates or highly qualified people to encourage yielding seat behaviors as they were reluctant to yield seats, possibly because of their busy life routine.…”
Section: Discussionsupporting
confidence: 91%
“…There are no significant differences in gender and living cost variations in keeping/giving seats to vulnerable individuals when holding all other variables constant, as illustrated in Table 4. Previously, Zhang et al found variations in the significant effects of gender differences for various anti-social behaviors, indicating that the significant differences in gender for conducting a behavior are subject to the type of the behavior itself ( 37 ). Therefore, it is reasonable to find no significant gender differences with regard to the decision to yield seats to vulnerable individuals.…”
Section: Resultsmentioning
confidence: 99%
“…The study adopted the structural equation modeling (SEM) approach by considering its suitability to test the hypothesis positing a relationship among latent constructs [46] and is also consistent with previous studies [8,47,48]. A series of models were built to identify the contributions of standard and extended components, such as PV and EC, in TAM to predict the intentions to adopt EMs.…”
Section: Analytical Approachmentioning
confidence: 99%